Pengaruh Kemudahan Penggunaan, Kepercayaan Konsumen, Kualitas Tampilan Dan Kualitas Informasi Terhadap Keputusan Pembelian Scarlett Whitening Melalui Promosi Di Tiktok (Studi Kasus Mahasiswa/I FEB UM Metro) - Durotun Nasikah; Jati Imantoro; Diah Prastika (Universitas Muhammadiyah Metro, 2024)
This research is motivated by the high use of the internet in Indonesia, used by many peopleas a promising business opportunity. This can be seen from the many online stores that havesprung up on social media which are believed to be effective as a medium for promotingproducts, one of the social media currently widely used by the public is Tiktok. The purposeof this study was to determine the effect of ease of use, consumer trust, display quality andinformation quality on purchasing decisions. In this study, it was tested using multiple linearregression analysis calculations using the SPSS20 program. This type of research isquantitative research or verification research. Quantitative research is research that usesnumbers, and in this study there were 68 respondents. The data analysis technique used inthis research is multiple linear regression. The results showed that: 1) The ease of usevariable had a positive effect on purchasing decisions. 2) The variable of consumerconfidence has a positive effect on purchasing decisions. 3) The display quality variable hasa negative effect on purchasing decisions. 4) The information quality variable has a positiveeffect on purchasing decisions. 5) The variables of ease of use, consumer trust, quality of information has a positive effect on purchasing decisions, while the quality of display doesnot have a positive effect on purchasing decisions.